Quality evaluation of selected tools to automate application testing - Szczepkowicz, Łukasz; Pańczyk, Beata (Journal of Computer Sciences Institute, 2018)
The subject of this article is a comparison of selected tools for the implementation of software tests. Seven open source tools were selected for the analysis: Selenium IDE, Selenium WebDriver, JMeter, SoapUI, SikuliX, AutoIT, Katalon Studio. The research was carried out using dedicated test applications (desktop, web and web service) with the same functionality.